EFISIENSI PENGGUNAAN INPUT PRODUKSI PADA USAHATANI BAWANG MERAH VARIETAS LEMBAH PALU DI DESA BULUPOUNTU JAYA KECAMATAN SIGI BIROMARU KABUPATEN SIGI (Studi Kasus Di Desa Bulupountu Jaya, Kecamatan Sigi Biromaru, Kabupaten Sigi) - Wahida Wahida; Made Antara; Rustam Abd Rauf (Universitas Tadulako, 2015)
This research aims to test the efficiency by using inputs production and analyse farming income of Bawang Merah Varietas Lembah Palu which managed by farmers in Bulupountu Jaya village. Bawang merah is one of vegetable commodity that has big market ooportunity in agricultural sector. The results by hypothesis testing of input production which are, area (X1), seeds (X2), fertilizer (X3), and labour (X4) simultanly and parsially are influencing positive and highly significant. All variables of inputs production, area (X1), seeds (X2), fertilizer (X3), and labour (X4), there are three inputs production haven’t allocated efficiently. They’re area, seeds, and fertilizer. While labours (X4) has allocated efficiently. So, from all of variables which have analysed, labour is the only one of inputs production that has allocated efficiently. Farming of Bawang Merah Varietas Lembah Palu earns income as Rp. 21.746.480,24/0,34 Ha or Rp. 64.634.792,65/Ha. Elegibility of farming based on analyzing R/C > 1 or as 2,66, it means farming of bawang merah varietas lembah Palu competend to laboured. Key words : Bawang Merah Varietas lembah Palu, Efficiency by using inputs production, inc